A novel integrated material flow cost accounting (MFCA)- IoT-lean management system approach to improving water use efficiency and reducing costs in the beverage industry - Thanwarhat Sodkomkham; Chavalit Ratanatamskul; Achara Chandrachai (Cleaner Environmental Systems)
The purpose of this study is to present a novel approach of integrating Material Flow Cost Accounting (MFCA), Internet of Things (IoT) and lean management systems to improve water use efficiency and reduce costs in the beverage industry. The positive and negative product costs of water purification, syrup manufacture, concentrate mixing, and packing were analyzed. The MFCA analysis showed 78.5% positive and 21.5% negative product costs. The use of the Power BI application to display real-time positive and negative costs in each process, scenario modeling and simulation was able to promote water savings and cost reductions, as well as supporting factory team ideation for choosing one of three improvement plans: 1) RO flushing water recovery in water purification; 2) water conservation with automated pH correction at packaging warmer; or 3) wastewater treatment and reuse of the rejected RO brine. According to our two-scenario water conservation testing, an automation process could improve pH adjustment in the packaging process, while MFCA, IoT, and lean management systems could be applied to improve industrial water use efficiency, demonstrating the potential for sustainable water use. The beverage-industry case in the present study validated this approach, resulting in a 24.1% production rate increase and a 4.5% cost reduction of 71,010 THB savings per year.